Quality of growth and poverty incidence in low income countries: The role of manufacturing - Sarah Lynne S. Daway; Geoffrey M. Ducanes; Raul V. Fabella (University of the Philippines, School of Economics (UPSE), 2017)
There has been a growing conversation about the revival of Manufacturing to push back growing inequality and reduce poverty. We discuss the pathways by which a higher share of the Manufacturing sector in GDP may bring about lower poverty incidence while a higher share of Services may have the opposite effect. We first compare the poverty reduction experiences of the Philippines whose growth has been largely Services-led in the last two decades with that of China and Vietnam, whose growth have, for the most part, been Manufacturing-led. We then present evidence based on cross-country panel data for low income countries that the Manufacturing share in GDP exhibits a significant negative association with poverty incidence while the higher Services share exhibits a significant positive association with poverty incidence. Low income countries seeking more inclusive growth may do better if they privilege their Manufacturing sector over the Services sector.
Keywords: O14; I3; O5; 330; quality of growth; low income countries; poverty incidence; industrial structure; manufacturing; services